Dynamics of the Ecuadorian population in the intercensal period 1974-1982 - Cadena Alvarado, Rosario (Revista Universidad de Guayaquil, 1990)
The difficulties of our country derive from the high rate of growth of its population. In Ecuador there are 25 different natural life zones, each of which has a peculiar ecological characteristic. In its four different natural regions we find a variety of climates, topography and soils, with extensive forests and large and numerous rivers. 70% of the national territory has agricultural and forestry vocation.